PENGEMBANGAN PERANGKAT PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPS MATERI MASALAH SOSIAL KELAS IV SEKOLAH DASAR - Qurun In Evri Lilasari Muhari Suhanadji (Forum Ilmu Sosial)
The background of this research is the fact that there are still many teachers used device learning without innovation so the critical thinking students' ability.  The purpose of this research to describe the validity and the effectiveness of device learning and to know difference in the critical thinking ability between the students who were taught used learning inquiry with the students who were taught in a talk method. This research was conducted using research and development with 4D model Thiagarajan (1974) with control group pretest-posttest design which produces device inquiry learning such as implementation learning, students' worksheet, and the result test which reflectif the critical thinking students' ability. The subject of this research were the students of four graders of Elementary School. The instrument used in this research were validation, implementation learning observation sheet, student activity sheet, and test. The validation results show device learning was 4.3 with very valid category. The learning implementation got a percentage of 88.5% which shows very good category, the students activity got a percentage of 87.97% which shows very good category and test got 80.16 > 75 which show increased. So, the development device learning can be taken effective. A difference in the critical thinking ability between the students who were taught used learning inquiry with the students who were taught in a talk method with T-Test got the significance was 0.031 < 0.05.